Modification and Assessment of the Bedside Pediatric Early Warning Score in the Pediatric Allogeneic Hematopoietic Cell Transplant Population. Issue 5 (May 2018) - Cater, Daniel T.; Tori, Alvaro J.; Moser, Elizabeth A. S.; Rowan, Courtney M.
Abstract : Objectives: To determine the validity of the Bedside Pediatric Early Warning Score system in the hematopoietic cell transplant population, and to determine if the addition of weight gain further strengthens the association with need for PICU admission. Design: Retrospective cohort study of pediatric allogeneic hematopoietic cell transplant patients from 2009 to 2016. Daily Pediatric Early Warning Score and weights were collected during hospitalization. Logistic regression was used to identify associations between maximum Pediatric Early Warning Score or Pediatric Early Warning Score plus weight gain and the need for PICU intervention. The primary outcome was need for PICU intervention; secondary outcomes included mortality and intubation. Setting: A large quaternary free-standing children's hospital. Patients: One-hundred two pediatric allogeneic hematopoietic cell transplant recipients. Interventions: None. Measurements and Main Results: Of the 102 hematopoietic cell transplant patients included in the study, 29 were admitted to the PICU. The median peak Pediatric Early Warning Score was 11 (interquartile range, 8–13) in the PICU admission cohort, compared with 4 (interquartile range, 3–5) in the cohort without a PICU admission ( p < 0.0001). Pediatric Early Warning Score greater than or equal to 8 had a sensitivity of 76% and a specificity of 90%. The area under the receiver operating characteristics curve was 0.83. There was a high negative predictive value at this Pediatric Early Warning Score of 90%. When Pediatric Early Warning Score greater than or equal to 8 and weight gain greater than or equal to 7% were compared together, the area under the receiver operating characteristic curve increased to 0.88. Conclusions: In this study, a Pediatric Early Warning Score greater than or equal to 8 was associated with PICU admission, having a moderately high sensitivity and high specificity. This study adds to literature supporting Pediatric Early Warning Score monitoring for hematopoietic cell transplant patients. Combining weight gain with Pediatric Early Warning Score improved the discriminative ability of the model to predict the need for critical care, suggesting that incorporation of weight gain into Pediatric Early Warning Score may be beneficial for monitoring of hematopoietic cell transplant patients.